Synthesis of Tetrahydro Pentagavunon-0 - Ritmaleni, Ritmaleni; Simbara, Ari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Curcumin, tetrahydrocurcumin, and monoketone curcumin analogue, pentagamavunone-0 (PGV-0), have been investigated as antioxidant, antiinflammatory and anticancer. This research was aimed to synthesise the Tetrahydropentagamavunone-0 (THPGV-0) compound which assumed as an active metabolite of PGV-0. The hydrogenation reaction was applied to the synthesis of THPGV-0 from PGV-0 using Pd/C 10 % as catalyst at room temperature. The structure elucidation was analysed by using spectroscophy method. The synthetic result showed that THPGV-0 asa white crystalline powder in 25 % with melting point about 122-123 oC.Key words: pentagamavunone-0, Tetrahydropentagamavunone-0, hydrogenation